2012
DOI: 10.1111/j.1740-0929.2012.01035.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between lactic acid bacteria and yeasts in airag, an alcoholic fermented milk

Abstract: The interaction between nine lactic acid bacteria (LAB) and five yeast strains isolated from airag of Inner Mongolia Autonomic Region, China was investigated. Three representative LAB and two yeasts showed symbioses were selected and incubated in 10% (w/v) reconstituted skim milk as single and mixed cultures to measure viable count, titratable acidity, ethanol and sugar content every 24 h for 1 week. LAB and yeasts showed high viable counts in the mixed cultures compared to the single cultures. Titratable acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 34 publications
(51 reference statements)
2
16
0
Order By: Relevance
“…mesenteroides enhances ethanol production from yeasts by supplying lactose‐hydolysates, glucose and galactose, in airag (Sudun et al . ). In addition to the promoting effect, this study suggests that Leu .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…mesenteroides enhances ethanol production from yeasts by supplying lactose‐hydolysates, glucose and galactose, in airag (Sudun et al . ). In addition to the promoting effect, this study suggests that Leu .…”
Section: Discussionmentioning
confidence: 97%
“…We recently revealed that these LAB and yeasts contribute to the fermentation with cooperatively or competitively affecting the growth and the metabolism of each other (Sudun et al . ). Health‐promoting effects of airag and koumiss, which include prevention of several diseases such as hypertension, gastroenteritis and tuberculosis, have been experimentally demonstrated.…”
Section: Introductionmentioning
confidence: 97%
“…Dekkera (61.92%) dominated in H1, and Dipodascus (99.79%) dominated in H2. These predominant genera in 10 samples belong to yeasts, and Kluyveromyces, Saccharomyces, Dipodascus, Kazachstania, and Dekkera play important roles in the processes of proteolysis, lipolysis, flavor emergence, lactic acid utilization, alcohol production, and fermentation of dairy products (Narvhus and Gadaga, 2003;Landell et al, 2006;Sudun et al, 2013;Sun et al, 2014). Nonetheless, Penicillium (42.14%), a genus of filamentous fungus, was the major genus in X2.…”
Section: Fungal Community Profile Of Koumissmentioning
confidence: 99%
“…LAB strains produce various antibacterial substances, including organic acids (such as lactic acid and propionic acid), hydrogen peroxide, diacetyl, carbon dioxide, and bacteriocins (Ayad, Verheul, Wouters, & Smit, ; Cheung, Huang, & Yu, ; Sudun, Wulijideligen, Arakawa, Miyamoto, & Miyamoto, ). Pathogenic bacteria including Bacillus anthracis , Listeria monocytogenes , Escherichia coli O157:H7, and Salmonella enterica Enteritidis can cause infectious diseases resulting in zoonosis of domesticated animals.…”
Section: Introductionmentioning
confidence: 99%